Abstract Assassination: How Police Militarization Has Contributed to the Rise of “Swatting” - Carrico, Lucas A. (2018)
In recent decades, police militarization has firmly planted itself at the forefront of academic discourse in institutions of higher learning around the globe. Various stances, positions, and theories have been extolled as to its origins, implications, and repercussions; however, this decade has produced what is arguably the most tangible embodiment of police militarization as a whole: swatting. Ostensibly a prank, this phenomenon entails the false reporting of a serious crime with the covert intention of this report being to direct as many heavily armed police officers to a location as possible. This phenomenon has become increasingly popular in the world of online gaming, with many perpetrators seeking to settle scores or exact revenge for breaches of gaming etiquette on individuals that are often a considerable distance away from them. Within the last decade, several deaths have resulted and numerous close calls have been brought to light following intense media coverage of high-profile incidents, including several instances involving celebrities. While policy makers scramble to assign blame and institute plans to circumvent the loss of any additional lives, many fail to recognize that this is merely the latest symptom of a desperately ill criminal justice system. This thesis will demonstrate that swatting is the latest in a string of increasingly overt side effects of the militarization of police. To this end, both contemporary and historical sources will be used to illustrate swatting’s lineage; as well as to provide a prism through which to contemplate possible solutions to this alarming new trend